An analytical framework for the Post-Keynesian macroeconomic paradigm - Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2013)
The original Keynesian paradigm differs from the Neoclassical Synthesis and even more so from the New-Keynesian approach. In this paper, a modern framework for the original Keynesian paradigm is presented. It will highlight the key elements of the paradigm. A model is developed to determine output, unemployment and price level changes. Finally, the paper draws policy conclusions based on Keynesian original thinking. The purpose of the paper is not only to give a framework of Keynesian thought, but also to stimulate debate and discussion within the Post-Keynesian camp. The paper is written in a way which allows nonexperts in the field to follow the argumentation. However, not all ramifications of the Post- Keynesian paradigm can be covered.
Keywords: E12; E20; E31; E50; E58; 330; economic paradigm; Keynesian economics; output and employment; inflation; economic policy